2016
DOI: 10.1002/clen.201500299
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead and Zinc From Contaminated Soil by a Novel Chelating Surfactant

Abstract: In the present study, the focus was to explore the feasibility of using a chelating surfactant, sodium N-lauroyl ethylenediamine triacetate (LED3A), as an effective washing reagent for lead (Pb)-and zinc (Zn)-contaminated soils. The total content of Pb and Zn was equal to 949.6 and 936.4 mg kg À1 , respectively. A series of batch washing experiments was conducted. The results showed that the washing experiments reached equilibrium within 17 h, at >3 g L À1 LED3A. The desorption processes of Pb and Zn could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It was observed that LED3A readily extracted metal from the acid extractable fraction, and partially also from the reducible, the oxidizable and the residual one. Qiao et al [41] also reported that LED3A had the ability to remove various forms of heavy metals in the soils. However, the difference in this study was that the proportion of Cu in the oxidizable fraction of washed soil decreased markedly, which possibly attribute to the enhanced solubilizing effect of surfactant on PAH in metal-PAH-soil bond [7].…”
Section: Effect Of Led3a Washing On Cumentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that LED3A readily extracted metal from the acid extractable fraction, and partially also from the reducible, the oxidizable and the residual one. Qiao et al [41] also reported that LED3A had the ability to remove various forms of heavy metals in the soils. However, the difference in this study was that the proportion of Cu in the oxidizable fraction of washed soil decreased markedly, which possibly attribute to the enhanced solubilizing effect of surfactant on PAH in metal-PAH-soil bond [7].…”
Section: Effect Of Led3a Washing On Cumentioning
confidence: 98%
“…Based on the kinetics parameters of Table 2, the decrease in the k di value of Cu or Phe reveals that the second stage of the multi-linear plot is the rate-limiting step. The increase in the c i value reflects the expanding in the thickness of the boundary layer surrounding the particle, which decreases the change in the external mass diffusion and increases the change of the internal mass transfer [41]. Such a multi-linearity curve with nonzero intercept demonstrated that intra-particle diffusion was not the only rate controlling step for the system [40,42].…”
Section: Desorption Kineticsmentioning
confidence: 99%
“…Chen et al found that the best removal efficiencies of Cd in artificially contaminated soil were obtained with 1 h washing time, and the Cd removal rate was achieved at 81.2% [55]. SDS can bind with metals and prompt their desorption from soil particles [56]. Other commonly used surfactants include DPC, DDAC, SDBS, Ammonyx KP, CATB, etc.…”
Section: Chemical (Synthetic) Surfactantsmentioning
confidence: 99%